A new species and molecular phylogeny of Brazilian succulent Euphorbia sect. Brasilienses. Issue 7 (3rd October 2018) - Hurbath, Fernanda; Leal, BÁrbara SimÕes Santos; Da Silva, Otávio Luis Marques; Palma-Silva, Clarisse; Cordeiro, INês
Abstract : A new species of Euphorbia sect. Brasilienses V.W. Steinm. & Dorsey is described. Euphorbia tetrangularis Hurbath & Cordeiro is endemic to the Serra de Montevidéu, a part of the Espinhaço Range located in the state of Minas Gerais, Brazil. It differs from other species within the section based on the following characters: 4-ribbed branches, green cyathia, and green cyathial glands with erect appendages. This new species would qualify as critically endangered (CR) according to IUCN criteria. An inferred phylogeny based on a combined dataset of nuclear (ITS1) and plastid regions ( psbA-trnH, trnC-ycf6, matK, atpI-atpH, psbJ-petA, trnQ-rps16 × 1 ) confirms the monophyly of Euphorbia sect. Brasilienses and supports the recognition of E. tetrangularis . The phylogeny also suggests that this group probably underwent a recent radiation.